[OP.1B.01] VITAMIN K DEPENDENT PROTECTION OF RENAL FUNCTION IN MULTI-ETHNIC POPULATION STUDIES. (September 2016) - WEI, F.; Drummen, N.E.A.; Schutte, A.E.; Thijs, L.; Jacobs, L.; Petit, T.; Yang, W.Y.; Smith, W.; Zhang, Z.Y.; Gu, Y.M.; Kuznetsova, T.; Verhamme, P.; et al.
Abstract : Objective: Vitamin K (VK) dependent carboxylation of matrix Gla protein (MGP) protects the macrocirculation against calcification. Whether glomerular filtration (GFR), a renal microvascular trait, is related to circulating desphospho-uncarboxylated MGP (dp-ucMGP) has not been explored before. We therefore investigated our hypothesis in our Flemish Study on Environment, Genes and Health Outcomes (FLEMENGHO) and sought replication in the South African Study Regarding the Influence of Sex, Age and Ethnicity on Insulin Sensitivity and Cardiovascular Function (SAfrEIC). Design and method: We determined plasma dp-ucMGP in 1166 white Flemish (mean age, 38.2 years) and 714 South Africans (49.2 % blacks; 40.7 years) and total uncarboxylated MGP (t-ucMGP) in Flemish only. dp-ucMGP increases with VK deficiency and t-ucMGP decreases with the extent of arterial calcification. We correlated estimated GFR (CKD-EPI) and stage of chronic kidney disease (KDOQI) with circulating MGP, using multivariable linear and logistic regression. Results: Among Flemish and Africans, GFR averaged 89.5 and 110.9 mL/min/1.73 m 2 and dp-ucMGP 3.68 and 7.0 μg/L, respectively. For a doubling of dp-ucMGP, GFR expressed in mL/min/1.73 m 2, decreased by 1.46 (p = 0.023) in Flemish and by 2.55 (p = 0.0007) in Africans. Among Flemish, 46.6%, 48.3% and 5.2% were in stage 1, 2 or 3 of chronic kidney disease, while among Africans, these proportions were 80.2%, 18.1%, and 1.7%, respectively. The odds of moving up one stage associated with a doubling of dp-ucMGP were 1.17 (p = 0.033) in Flemish and 1.19 (p = 0.16) in Africans. In Flemish, doubling of dp-ucMGP and t-ucMGP were independently associated with changes in GFR amounting to −1.42 mL/min/1.73 m 2 (95% confidence interval [CI], −2.66 to −0.19) and 1.86 (CI, 0.03 to 3.68), respectively. Conclusions: In the general population, GFR decreases and the risk of renal impairment increases with higher dp-ucMGP, a marker of VK deficiency, whereas the opposite is the case for t-ucMGP, a marker of arterial calcification. These findings potentially highlight new avenues for promoting renal health, for instance by vitamin K supplementation.